2014 IEEE/ION Position, Location and Navigation Symposium - PLANS 2014 2014
DOI: 10.1109/plans.2014.6851497
|View full text |Cite
|
Sign up to set email alerts
|

Study of MEMS-based inertial sensors operating in dynamic conditions

Abstract: Abstract-This paper aims at studying the behaviour of the errors coming from inertial sensors when measured in dynamic conditions. After proposing a method for constructing the error process, the properties of these errors are estimated via the Generalized Method of Wavelets Moments methodology. The developed model parameters are compared to those obtained under static conditions. Finally an attempted is presented to find the link between the encountered dynamic of the vehicle and error-model parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The correlation of IMU errors with system dynamics is a topic of great importance that may increase with the spreading use of low-cost inertial sensors. Recent studies confirmed that system dynamics may have an important influence on the characteristics of the error signal issued from inertial sensors (see [26]). The possibility of adapting noise models according to the dynamics that the system is subject to should therefore be considered in the navigation filters to enhance the performance of stochastic modeling.…”
Section: B Calibration Under Dynamicsmentioning
confidence: 86%
“…The correlation of IMU errors with system dynamics is a topic of great importance that may increase with the spreading use of low-cost inertial sensors. Recent studies confirmed that system dynamics may have an important influence on the characteristics of the error signal issued from inertial sensors (see [26]). The possibility of adapting noise models according to the dynamics that the system is subject to should therefore be considered in the navigation filters to enhance the performance of stochastic modeling.…”
Section: B Calibration Under Dynamicsmentioning
confidence: 86%
“…Proper crash test recording thus requires specially designed components [7]. More recent work [8], [9] studies behavior of low-cost inertial micro-electro mechanical sensors (MEMS) in dynamic conditions. One of the findings is that characteristics of the rate gyroscopes are more stable than of the accelerometers.…”
Section: Introductionmentioning
confidence: 99%